Clinical outcome and MRI appearance in a group of chronic low back pain patients more than 10 years after discography evaluation and consideration for surgery - Hanna Hebelka; Veronica Gunterberg; Kerstin Lagerstrand; Helena Brisby (BMC Musculoskeletal Disorders, 2023)
Abstract Background It is an ongoing debate whether fusion surgery is superior to non-operative treatment for non-specific low back pain (LBP) in terms of patient outcome. Further, the evidence for how signs of intervertebral disc (IVD) degeneration on magnetic resonance imaging (MRI) correlate with patient outcome is insufficient. Longitudinal studies of low back pain (LBP) patients are thus of interest for increased knowledge. The aim of this study was to investigate long-term MRI appearance in LBP patients 11–14 years after discography. Methods In 2021, 30 LBP patients who had same-day discography and MRI in 2007–2010 were asked to undergo MRI (Th12/L1–L5/S1), complete visual analog scale (VAS), Oswestry Disability Index (ODI) and EuroQol-5 Dimension (EQ5D) questionnaires. Patients who had fusion surgery before the follow-up were compared with those without such surgery. MRIs were evaluated on Pfirrmann grade, endplate classification score (EPS), and High Intensity Zones (HIZ). For each disk it was noted if injected at baseline or not. Results Of 17 participants (6 male;mean age 58.5 years, range 49–72), 10 (27 disks) had undergone fusion surgery before the follow-up. No differences in VAS, ODI, or EQ5D scores were found between patients with and without surgery (mean 51/32/0.54 vs. 50/37/0.40, respectively; 0.77 > p < 0.65). Other than more segments with EPS ≥ 4 in the surgery group (p < 0.05), no between-group differences were found in longitudinal change in MRI parameters. Of 75 non-fused disks, 30 were injected at baseline. Differences were found between injected and non-injected disks at both baseline and follow-up for Pfirrmann grade and HIZ, and at follow-up for EPS (0.04 > p < 0.001), but none for progression over time (0.09 > p < 0.82). Conclusions Other than more endplate changes in the surgery group, no differences in longitudinal change of MRI parameters were established between LBP patients treated with or without fusion surgery in the studied cohort. The study also highlights the limited progress of degenerative changes, which may be seen over a decade, despite needle puncture and chronic LBP.